Impact of Gut Microbiota on the Development of Diseases - Karolina Winiarek; Martyna Michalska; Wiktor Wardyn; Cezary Guzowski; Joanna Anna Murawska; Daria Ziemińska; Rafał Burczyk; Kornelia Kędziora-Kornatowska (Nicolaus Copernicus University in Toruń, 2024)
Aim: The aim of this article is to review the latest scientific research on the influence of intestinal microbiota on the development of diseases. In this article we will discuss the importance of the intestinal microbiota, the differences in the composition of the microbiota between healthy and sick people and the relationship between the intestinal microbiota and metabolic, inflammatory, cardiovascular and neurodegenerative diseases. Abbreviated description of the state of knowledge: The gut microbiota plays a key role in human health by influencing the development and progression of various diseases. Numerous studies have shown that an imbalance in gut microbiota, called dysbiosis, may be linked to a number of conditions. Intestinal microflora interacts with the immune system, modulates inflammation and influences metabolic pathways, which emphasizes its importance in the development of diseases. Conclusions: Intestinal microflora is crucial to health, regulating immune, metabolic and neurological functions. Dysbiosis, i.e. disturbance of the balance of intestinal microflora, is associated with diseases such as type 2 diabetes, obesity, inflammatory bowel diseases, allergies, autoimmune diseases and neuropsychiatric disorders. Healthy microflora, influenced by diet, pH and nutrients, are essential for metabolism, immune system regulation and neuronal communication. Recently, scientists have become interested in the possibility of using this knowledge in treatment. Appropriate dietary management, probiotic supplementation and fecal microflora transplantation show promising potential. Future research should focus on elucidating the specific mechanisms by which the gut microbiota influences disease processes and developing targeted therapies to exploit the therapeutic potential of the microbiota.